PENGARUH PENERAPAN MODEL INKUIRI TERBIMBING BERBANTUAN E-MODUL TERHADAP PEMAHAMAN KONSEP HIDROLISIS GARAM - Hariani, Nur Rizkhana; Nuswowati, Murbangun; Winarno, Winarno (Jurnal Inovasi Pendidikan Kimia, 2020)
Concept understanding of student in Indonesia shows a relatively low percentage of 42,5%. Guided inquiry combined with e-module becomes an alternative learning that is applied because it is able to student to develop concepts through scientific methods. This study aims to determine the effect of the application of the guided inquiry learning model assisted by e-module towards student’s concept understanding. This experimental research uses quantitative descriptive methods. The population in this study is students of class XI MIPA SMAN 3 Pati in the academic year 2018/2019. The sample in this study was taken by purposive sample technique. The sample in this study is students of class XI MIPA 1 as an experimental class an XI MIPA 2 as a control class. This study uses a pretest-posttest group design. Data collection techniques were carried out using a three tier multiple choice model test, interview sheets and questionnaires. Hypothesis testing is done using the two different test, test the effect of variables and n-gain test. The results showed that the average concept understanding of experimental class was higher than control class. Great increase in concept understanding of experimental class is 0.50, into medium category. The results of questionnaire responses analysis showed that students give positive renponses regarding the learning model applied. The result shows that the application of the guided inquiry learning model assisted by e-module has a positive influence that can improve concept understanding of student.